2005
DOI: 10.1007/s10535-005-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose accumulation and enzyme activities in callus culture of sugarcane

Abstract: The activities of sucrose phosphate synthase (SPS), sucrose synthase (SUSY), neutral invertase (NI) and soluble acid invertase (SAI) were measured in callus cultures of four Mexican sugarcane cultivars (Saccharum spp.) with a different capacity to accumulate sucrose in stem parenchyma cells. The results indicated that sucrose accumulation in callus was positively correlated to the activity of SPS and SUSY and negatively to the activity of SAI and NI while SPS explained most of the variation found for sucrose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
3
7
1
Order By: Relevance
“…The similar patterns of sugar accumulation were also shown in banana, kiwifruit and citrus (Langenkämper et al, 1998;Komatsu et al, 1999;Ménager et al, 2004). The contrary findings of SPS activity in other fruits indicated that different biochemical pathways participated into sugar accumulation (Gutierrez-Miceli et al, 2005;Grof et al, 2006).…”
Section: Sugar Accumulation and Metabolic Enzymes Analysissupporting
confidence: 55%
“…The similar patterns of sugar accumulation were also shown in banana, kiwifruit and citrus (Langenkämper et al, 1998;Komatsu et al, 1999;Ménager et al, 2004). The contrary findings of SPS activity in other fruits indicated that different biochemical pathways participated into sugar accumulation (Gutierrez-Miceli et al, 2005;Grof et al, 2006).…”
Section: Sugar Accumulation and Metabolic Enzymes Analysissupporting
confidence: 55%
“…; Gutierrez‐Miceli et al . ) and shown to have a pivotal role in carbohydrate metabolism. Usually, sucrose synthesised in the cytosol is partitioned either for export or for storage in the vacuole (Winter et al .…”
Section: Introductionmentioning
confidence: 99%
“…Acid invertase exists as a soluble form in the vacuole (SAI) and as a cell wall-bound (CWI) form, but is totally absent from the cytosol (Walker & Pollock 1993). The role of invertase, especially SAI, in regulating the sucrose content in leaves has been extensively studied (Scholes et al 1996;Gutierrez-Miceli et al 2005) and shown to have a pivotal role in carbohydrate metabolism. Usually, sucrose synthesised in the cytosol is partitioned either for export or for storage in the vacuole (Winter et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the primary translocatable carbohydrate in the majority of plants, the accumulation of sucrose is vital to the initiation of increased freezing tolerance (Strand et al 2003). Enzymes, such as sucrose-phosphate synthase, sucrose synthase, neutral invertase and soluble acid invertase, are directly involved in sucrose synthesis and degradation (Gutierrez-Miceli et al 2005). The alterations of these enzymes have been investigated in plants exposed to low temperatures; however, the activities of these enzymes at low temperatures vary greatly among plant species (Guy et al 1992;Tognetti et al 1989).…”
Section: Introductionmentioning
confidence: 99%